Some New Existence and Uniqueness Results for an Integral Boundary Value Problem of Caputo Fractional Differential Equations - Haixing Feng; Chengbo Zhai (Discrete Dynamics in Nature and Society)
In this work, we consider an integral boundary value problem of Caputo fractional differential equations. Based on a fixed-point theorem of generalized concave operators, we obtain the existence and uniqueness of positive solutions. As applications of main results, we give two examples in the end.